Genetics in Sustainable Fisheries Management - Saleem Mustafa (Wiley Blackwell, 1999)
Recent years have witnessed a surge of interest in the application of the principles of genetics to conservation and the sustainable management of fish resources. The realization of the genetic basis of many fisheries management problems is growing at a time when the world catch from fisheries is approaching the maximum sustainable level and all levels of biodiversity are threatened. Contributions from an international authorship are based on the latest scientific information on tropical and temperate ecosystems and their fish resources, and provide a detailed account of the genetic profiles of different fish populations, molecular genetic marking techniques, factors affecting genetic diversity , and genetic manipulation techniques. The book sets out to apply conservation and biotechnology to protect natural fish populations and wild fish gene pools while addressing the issues concerning biosafety and sustainable management.